IMPLEMENTASI PROGRAM PERLUASAN JANGKAUAN PEMASARAN UMKM PADA DINAS PERDAGANGAN KOTA SURABAYA - Merah Mega Pertiwi; Suci Megawati (Publika, 2021)
The MSME marketing reach expansion program created by the Department of Trade aims to revive the UMKM in Surabaya which has long been drowning. The purpose of this study is to find out the implementation of the MSME marketing reach expansion program at the Department of Trade. The results of the research obtained were who was involved in the program, who participated in the program, namely the Trade Service and companions, tailors on Jalan Patua and the Bukit Barisan sewing center, the community, and security officers. The essence of the program administration process is socialization from the Trade Office regarding the area around Jalan Patua so that it is clean and has a wide road. And there are requirements that are needed for tailors to move to the Bukit Barisan sewing center, namely having a Surabaya ID card because the majority of the tailors are domiciled in Madura. Compliance with a program is due to the lack of strategic location of the center building, resulting in tailors who have been moved to the SME center returning to Jalan Patua. The effect or impact of the program implementation is that the number of tailors at the sewing center of the Bukit Row was originally 50 and now there are 11 tailors left. The income for the tailors of the Bukit Barisan sewing center has decreased drastically, and there are also those who do not get wages every day. This is because the location experiences a fairly shallow flood when the rainy season arrives, the street lighting is also minimal, and there is less attention. Then access roads that are difficult to reach by entering the alley first and the center building next to the TPA.Keywords: Implementation, Marketing Reach Extension Program, micro, small and medium enterprises Program perluasan jangkauan pemasaran UMKM dibuat oleh Dinas Perdagangan bertujuan untuk menghidupkan kembali UMKM di Surabaya yang sudah lama tenggelam, tujuan penelitian ini yaitu mengetahui implementasi program perluasan jangkauan pemasaran UMKM pada Dinas Perdagangan. Hasil penelitian yang di dapat adalah siapa yang dilibatkan dalam program, yang berpartisipasi dalam program yaitu Dinas Perdagangan dan pendamping, penjahit di Jalan Patua dan sentra ukm jahit bukit barisan, masyarakat, serta petugas keamanan. Hakikat proses administrasi program, adanya sosialisasi dari Dinas Perdagangan mengenai sekitar Jalan Patua agar bersih dan memiliki jalan yang lebar. Serta ada persyaratan yang diperlukan penjahit agar dapat pindah ke sentra jahit bukit barisan yaitu memiliki KTP Surabaya karena mayoritas penjahit berdomisili Madura. Kepatuhan atas suatu program yaitu karena kurang strategisnya letak gedung sentra mengakibatkan para penjahit yang sudah di pindahkan ke sentra ukm kembali lagi ke Jalan Patua. Efek atau dampak dari implementasi program yaitu jumlah penjahit di sentra jahit bukit barisan awalnya adalah 50 dan sekarang tersisa 11 penjahit. Untuk pengahsilan penjahit sentra ukm jahit bukit barisan mengalami penurunan drastis, dan juga ada yang tidak mendapatkan upah setiap harinya. Hal tersebut dikarenakan lokasi mengalami banjir yang lumayan dangkal jika musim hujan tiba, untuk lampu penerangan jalan yang juga minim, serta kurang diperhatikan. Kemudian akses jalan yang sulit di jangkau dengan memasuki gang terlebih dahulu dan gedung sentra bersebelahan dengan TPA. Kata Kunci: Implementasi, Program Perluasan Jangkauan Pemasaran, umkm